2011
DOI: 10.1177/0892705709095996
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Estimation of Buried Pipelines Using First-Order Reliability Method

Abstract: Corrugated polyethylene (PE) pipes are used widely for a variety of applications. These pipes provide substantial benefits over concrete, metal, and other traditional pipes in terms of their ability to resist environmental stresses from chemical and biological agents. Furthermore, they are easy to install, tough in the field, durable in service, and environmentally benign. In this article, the limit state function (LSF) is formulated in accordance with conventional design method. The first-order reliability me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Therefore, it was suggested that the non-destructive testing of the PE pipe should focus on the initial crack depth. Lee and Kim et al 22 performed a reliability assessment of corrugated polyethylene pipes utilizing three design criteria: deflection, bending stress, and bending strain. Furthermore, by employing the first-order reliability method, the failure probability of the pipes was utilized for evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it was suggested that the non-destructive testing of the PE pipe should focus on the initial crack depth. Lee and Kim et al 22 performed a reliability assessment of corrugated polyethylene pipes utilizing three design criteria: deflection, bending stress, and bending strain. Furthermore, by employing the first-order reliability method, the failure probability of the pipes was utilized for evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature several studies have been investigated related with the reliability of composite materials [16][17][18][19][20][21][22][23]. The reliability analysis of buried pipelines which are made of corrugated polyethylene was performed in [16] by using the first order reliability method Fig. 1 A schematic view of the pultrusion process with resin injection chamber (top) [1] and without resin injection chamber (bottom) (FORM).…”
Section: Introductionmentioning
confidence: 99%